Complications of oropharyngeal dysphagia in older individuals and patients with neurological disorders: insights from Mataró hospital, Catalonia, Spain - Karunaratne, Tennekoon B.; Clavé, Pere; Ortega, Omar (Frontiers in Neurology, 2024)
Background Oropharyngeal dysphagia (OD) significantly impacts older individuals and neurologically compromised patients, hindering safe ingestion of food and liquids. Despite its prevalence, OD remains underdiagnosed and undertreated, leading to severe complications such as malnutrition, dehydration, respiratory infections, and aspiration pneumonia (AP), and increases hospital readmissions. Objectives This study analyzes the intricate relationship between OD and various clinical complications in older individuals and patients with neurological disorders. Methods Utilizing retrospective analysis and narrative review, our work consolidates findings from prior studies on Hospital de Mataro’s dysphagia patient cohort. Revisiting OD’s intricate association with clinical complications, it presents data via odds ratios (OR), incidence ratios (IR), and hazard ratios (HR) from univariate and multivariate analyses. Results Five studies (2001–2014) involving 3,328 patients were scrutinized. OD exhibited independent and significant associations with various complications among older patients. Older individuals with OD faced heightened 1-month (ODDS 3.28) and 1-year (OR 3.42) mortality risks post-pneumonia diagnosis. OD correlated with a 2.72-fold risk of malnutrition, 2.39-fold risk of lower respiratory tract infections, 1.82-fold pneumonia readmissions (IR), and 5.07-fold AP readmissions (IR). Post-stroke OD is linked to neurological impairment (OR 3.38) and respiratory (OR 9.54) and urinary infections (OR 7.77), alongside extended hospital stays (beta coefficient 2.11). Conclusion Oropharyngeal dysphagia causes and significantly exacerbates diverse clinical complications in older and post-stroke patients, emphasizing the urgent need for proactive identification, comprehensive assessment, and tailored management. Acknowledging OD’s broader implications in general medical practice is pivotal to improving patient outcomes and healthcare quality.